2009
DOI: 10.1002/pssa.200982214
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence assessment of 0.5, 1.0 and 4.0 µm thick HFCVD undoped diamond films

Abstract: Chemical vapor deposition (CVD) diamond has not found extensive application as a thermoluminescence (TL) dosimeter, mainly because its TL glow curve shape is not reproducible. A slight variation in the growing conditions may result in strong changes in the morphology, microstructure, and surfaceimpurity-related defects, considerably affecting the TL glow curve features. In order to study the main TL characteristics under controlled growing conditions, we present results on three 0.5, 1.0, and 4.0 m thick hot f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The Raman spectroscopy is a fingerprint of each crystal structure, therefore it is an ideal and nondestructive tool for detection of different forms of crystalline and amorphous carbons, characterized by sp 2 and sp 3 hybridized C-C bonds [23] and for this reason it is also frequently used for the analysis of CVD diamond quality.…”
Section: Resultsmentioning
confidence: 99%
“…The Raman spectroscopy is a fingerprint of each crystal structure, therefore it is an ideal and nondestructive tool for detection of different forms of crystalline and amorphous carbons, characterized by sp 2 and sp 3 hybridized C-C bonds [23] and for this reason it is also frequently used for the analysis of CVD diamond quality.…”
Section: Resultsmentioning
confidence: 99%
“…Till date, the maximum work related to dosimetry studies on diamond has 2 remained confined to the films grown by microwave plasma assisted CVD and very little work has been done on the films grown by HFCVD method, especially the OSL part for un-doped diamond films prepared by this technique has not been reported in detail so far. It is worth mentioning here that the TL and OSL responses in diamond films grown by different methods cannot be compared exactly as the deposition condition has strong influence on the crystal structure, surface morphology, microstructure and defect or trap density in the deposited film which in turn can change the luminescence property completely [9]. In the TL/OSL dosimetry aspects of HFCVD grown diamond, the works reported by Goncalves et al [10] and Pedroza-Montero et al [11] are notable but they have used boron doped diamond.…”
Section: Introductionmentioning
confidence: 99%
“…The undoped diamond films are easy to prepare than the doped ones and thus the possibility of its use in radiation dosimeters need to be explored thoroughly. Some authors have reported TL of the undoped diamond films grown by HFCVD method [9,12]. In the present work, diamond films were formed by HFCVD method and the as deposited film was investigated for TL and OSL responses.…”
Section: Introductionmentioning
confidence: 99%
“…Most of studies are devoted to CVD diamond films grown on various substrates (see for instance ref. and references therein). Another synthetic diamond is high pressure–high temperature (HPHT) diamond that is commercially available since 1950s with main application as cutting and drilling tools.…”
Section: Introductionmentioning
confidence: 99%